Irrigation performance: Iraq - Amdar, Nafn; Talal, G.; Schmitter, Petra; Dembélé, Moctar (International Water Management Institute, 2025)
The Irrigation Performance Assessment Tool (IPAT) uses WaPOR data to assess water consumption, crop and water productivity, and irrigation performance. It provides insights on soil salinity impacts, water allocation, and efficiency indicators, supporting more effective agricultural planning and resource management in drought-affected areas.